Hubungan Usia dan Personal Hygiene dengan Kejadian Pedikulosis Kapitis - Patimah Patimah; Syamsul Arifin; Lisda Hayatie (Homeostasis, 2019)
Abstract: Pediculosis capitis is a health problem throughout the world, especially in school children who live in dorm. Personal hygiene is an important aspect in determining health status and age is one of the factors that influence health behavior. The purpose of this study was to determine the relationship between age and personal hygiene with the incidence of pediculosis capitis in Darul Hijrah Islamic Boarding School. The research method is observational analytic with cross sectional approach. The sample size of 50 respondents was using the stratified proportional random sampling technique. The results of the statistical test for age is p=0.003; PR=1,67 and personal hygiene is p=0.001; PR=0,64, so it can be concluded that there is a relationship between age and personal hygiene with the incidence of pediculosis capitis in Darul Hijrah Islamic Boarding School Martapura. Keywords: pediculosis capitis, age, personal hygiene. Abstrak: Pedikulosis kapitis menjadi masalah kesehatan di seluruh dunia terutama pada anak sekolah yang tinggal di asrama. Personal hygiene merupakan aspek penting dalam menentukan status kesehatan dan usia merupakan salah satu faktor yang mempengaruhi perilaku kesehatan. Tujuan penelitian untuk mengetahui hubungan usia dan personal hygiene dengan kejadian pedikulosis kapitis di Pesantren Darul Hijrah Puteri Martapura. Metode penelitian adalah observasional analitik dengan pendekatan cross sectional. Besar sampel 50 responden dengan teknik proportional stratified random sampling. Instrumen penelitian yang digunakan adalah kuesioner dengan uji statistik chi-square. Hasil uji statistik untuk usia didapatkan nilai p=0,003; PR=1,67 dan personal hygiene didapatkan nilai p= 0,001; PR=0,64, sehingga dapat disimpulkan terdapat hubungan antara usia dan personal hygiene dengan kejadian pedikulosis kapitis di Pesantren Darul Hijrah Puteri Martapura. Kata-kata kunci: pedikulosis kapitis, usia, personal hygiene.